Withdrawal severity and early response to treatment in the outpatient transition from opioid use to extended release naltrexone. (20th July 2018) - Mannelli, Paolo; Swartz, Marvin; Wu, Li‐Tzy
Abstract : Background and Objectives: Long acting naltrexone has improved the therapy of opioid use disorder (OUD), and safe and effective withdrawal management during naltrexone induction may help advance treatment. Despite the uncertain role of opioid withdrawal in predicting successful outcomes, early symptom control may favor detoxification completion. Methods: We explored withdrawal severity and early response to treatment, safety, and clinical measures in 35 adult patients with DSM‐5 OUD during a 7‐day office‐based buprenorphine‐naltrexone and ancillary medications transition to extended‐release naltrexone (XR‐NTX). Results: Subjective and objective measures of withdrawal intensity improved consistently throughout treatment in the whole sample. Participants who went on to receive XR‐NTX ( n = 27, 77%) reported a greater attenuation of symptoms by treatment day 2 ( r = .595, p = .001), and were less likely to be injection drug users ( r = −.501, p = .004). Adverse events (AEs) were recorded in 20% of participants: the majority ( n = 6, 85.7%) consisted of single episodes of increased withdrawal which were well controlled using ancillary medications. One serious AE was unrelated to treatment. Conclusions and Scientific Significance: Early opioid withdrawal changes may be a useful indicator of treatment response, helping adjust the transition protocol to the individual patients' need and gather valuable information for a better understanding of the relationship between initiating and remaining in treatment. (Am J Addict 2018;27:471–476)